Effects of the lumbar support function of wearable robot (Bot Fit) on sitting position - Jang-hoon Shin; Hyunmuk Lim; Naeun Byeon; Dokwan Lee; Hwang-Jae Lee; Wan-hee Lee (BioMedical Engineering OnLine)
Abstract Background Sedentary lifestyles can lead to musculoskeletal disorders, but proper sitting posture, particularly maintaining a slight anterior pelvic tilt, helps prevent issues like lower back pain and spinal misalignment. Samsung Electronics wearable robot ‘Bot Fit’ improves posture by enhancing core muscle tension, reducing trapezius muscle tension, and improving spinal alignment, which can alleviate pain and improve overall musculoskeletal health. Objective This study was conducted to evaluate the effectiveness of Samsung’s wearable robot, ‘Bot Fit’, in promoting proper sitting posture. Methods This study involved 37 participants, including healthy adults, elderly individuals. Participants were evaluated under two conditions, with and without the Bot Fit device, while seated on a Bobath table. Muscle tension, spinal angles, sitting height, and gluteal pressure distribution were measured under both conditions, and statistical analysis was conducted using paired t-tests with a significance level of p = 0.05. Results Participants showed a significant increase in sitting height and rectus abdominis muscle tone, while upper trapezius muscle tone significantly decreased (p < 0.05). Additionally, hip pressure increased across all regions, and pressure differences between the left and right hips decreased significantly (p < 0.01). Conclusion Wearing the Bot Fit with its posture correction function improved muscle tone and sitting posture in adults and the elderly, potentially helping to prevent secondary musculoskeletal disorders from poor posture. Future research should explore the optimal torque settings of the Bot Fit based on individual factors like weight and gender.